Robot z adaptivnim vodenjem za dvoročno vadbo hemiparetičnih pacientov - Trlep, Matic (Rehabilitacija (Ljubljana), 2010)
Background: Hemiparesis is the most common motor deficit following stroke. Bimanual training and robot assisted therapy are often used to regain motor functionality of the paretic limb. Methods: The goal of this pilot study was development and validation of a bimanual training system that stimulates the use of both arms of hemiparetic subjects. Adaptive assistance control adjusts the contribution of the unaffected arm, thus reducing the load on the paretic arm. Four chronic hemiparetic subjects participated in the study. They performed three different tracking exercises in bimanual mode and in two unimanual modes to validate the applicability of the system. The movements of the paretic limb must be coordinated with the unaffected limb to complete the bimanual exercise. Results: The bimanual robot training resulted in improvements of motor performance in terms of power ratio of both hands and task performance. The adaptive assistance control enabled the subjects to complete the exercises regardless of the level of their impairment. Conclusions: Adaptive control assisted the subjects in completing the movements while simultaneously stimulating the use of the paretic arm. Correlation between bimanual training and unimanual performance was observed.
Keywords: hemipareza; rehabilitacija; rehabilitacijska robotika; rehabilitation; Robotics; Stroke; Upper extremity; vocational rehabilitation